2018
DOI: 10.3389/fphys.2018.00647
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Light Therapy Protects Red Blood Cells Against Oxidative Stress and Hemolysis During Extracorporeal Circulation

Abstract: Aim: An activation of non-specific inflammatory response, coagulation disorder, and blood morphotic elements damage are the main side effects of the extracorporeal circulation (ECC). Red-to-near-infrared radiation (R/NIR) is thought to be capable of stabilizing red blood cell (RBC) membrane through increasing its resistance to destructive factors. We focused on the development of a method using low-level light therapy (LLLT) in the spectral range of R/NIR which could reduce blood trauma caused by the heart-lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 71 publications
1
15
0
1
Order By: Relevance
“…As demonstrated by Cury [93], PBM at 780 nm and 40 J/cm 2 triggered an increase in the expression of the protein HIF 1α and of vascular endothelial growth factor, and a decrease in matrix metalloproteinase 2 activity, all of which were found to induce angiogenesis. Additionally, in an in vitro study of the effects of red/NIR light on red blood cells, NIR light was found to be quite effective in protecting red blood cells from oxidation [94], which is a common occurrence in brains compromised by conditions such as MDD [95].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…As demonstrated by Cury [93], PBM at 780 nm and 40 J/cm 2 triggered an increase in the expression of the protein HIF 1α and of vascular endothelial growth factor, and a decrease in matrix metalloproteinase 2 activity, all of which were found to induce angiogenesis. Additionally, in an in vitro study of the effects of red/NIR light on red blood cells, NIR light was found to be quite effective in protecting red blood cells from oxidation [94], which is a common occurrence in brains compromised by conditions such as MDD [95].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…A wide range of studies on immune cells have demonstrated that direct tissue exposure to red/NIR light can reduce the influx of polymorphonuclear leukocytes into a targeted site of inflammation, thus decreasing the oxidative burst (de Lima et al, 2011;Oliveira et al, 2014;Walski et al, 2018). The remote neuroprotective action of bloodmediated effects of nostril based i-PBMT could be paradoxically related to modulation of reactive oxygen species (ROS) formation (Karu et al, 2005).…”
Section: Intranasal Photobiomodulation Therapy From the Nostrilsmentioning
confidence: 99%
“…The shear stress is the main causative mechanism for hemolysis during mechanical support, and some risk factors have been identified, such as the negative inlet pressure, pump speed, pump and oxygenator type, cavitation and priming solution (Steinhorn et al, 1989; Lou et al, 2014; Rother et al, 2005). In addition, oxidative stress is a determinant of hemolysis (Boyle et al, 1997; Walski et al, 2018). Lipid peroxidation and protein damage of cell membranes from ROS cause enzymatic inactivation, depolarization of the cell membrane and a change in its permeability, resulting in cell lysis (Matés et al, 1999; Kirkham and Rahman, 2006).…”
Section: Oxidative Stress and Ecmomentioning
confidence: 99%
“…Although the relative contribution of each circuit component on the hemolysis and related oxidative stress is unknown, the use of a centrifugal pump and small size connectors should be considered as potential sites of increased hemolysis (Lou et al, 2014; Williams et al, 2015). Furthermore, the use of red-to-infrared radiation (R/NIR) to stabilize erythrocyte membranes with increased resistance to oxidative stress seems promising (Itoh et al, 2000; Komorowska et al, 2001; Chludzińska et al, 2005; Walski et al, 2015, 2018).…”
Section: Oxidative Stress and Ecmomentioning
confidence: 99%